2021
DOI: 10.1371/journal.pone.0250321
|View full text |Cite
|
Sign up to set email alerts
|

CT-based determination of excessive visceral adipose tissue is associated with an impaired survival in critically ill patients

Abstract: Objective Obesity is a negative prognostic factor for various clinical conditions. In this observational cohort study, we evaluated a CT-based assessment of the adipose tissue distribution as a potential non-invasive prognostic parameter in critical illness. Methods Routine CT-scans upon admission to the intensive care unit (ICU) were used to analyze the visceral and subcutaneous adipose tissue areas at the 3rd lumbar vertebra in 155 patients. Results were correlated with various prognostic markers and both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 34 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…In reference to our study in critically ill patients, one could hypothesize that individual body composition might be associated with impaired long-term survival as initially low sRANKL levels might also affect bone metabolism and remodeling. Recent studies from our group highlighted the importance of the individual’s body composition reporting that excessive visceral adipose tissue, as well as sarcopenia and myosteatosis, are associated with poorer outcomes in critically ill patients [ 37 , 38 , 39 ], going in line with further studies discussing frailty as potential key determinant predicting complicated courses of disease and poorer long-term outcomes [ 40 ]. Numerous further functional pathways have been and are currently under investigation.…”
Section: Discussionmentioning
confidence: 76%
“…In reference to our study in critically ill patients, one could hypothesize that individual body composition might be associated with impaired long-term survival as initially low sRANKL levels might also affect bone metabolism and remodeling. Recent studies from our group highlighted the importance of the individual’s body composition reporting that excessive visceral adipose tissue, as well as sarcopenia and myosteatosis, are associated with poorer outcomes in critically ill patients [ 37 , 38 , 39 ], going in line with further studies discussing frailty as potential key determinant predicting complicated courses of disease and poorer long-term outcomes [ 40 ]. Numerous further functional pathways have been and are currently under investigation.…”
Section: Discussionmentioning
confidence: 76%
“…Studies have shown that preoperative BMI, sex, and anthropometric indicators can predict the effect of postoperative weight loss (26,27). Psychological factors, marital relationships, and social factors that influence dietary behavior have also been explored in other studies (28)(29)(30)(31). Abdominal adipose tissue is closely related to obesity and obesity related metabolic disorders, but its impact on postoperative weight loss has remained relatively unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…Computed tomography (CT) scan body composition analyses emerge as an attractive and potentially more reliable alternative in the ICU setting [41,42,64,[67][68][69]. Subsequently, a well-characterized subset of our ICU cohort underwent CT-scan body composition analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Reconstructed slice thickness was 5 mm and only venous-phase scans were used for body composition calculations. According to the literature, there is a strong association between single-slice measurements and total compartment volumes [40][41][42]. Hence, total visceral and subcutaneous adipose tissue (VAT, SAT), skeletal muscle area and its mean attenuation given in Hounsfield units (HU) were segmented at the center plane of the third lumbar vertebra on axial CT scans.…”
Section: Assessment Of Computed Tomography Scan Body Composition Markersmentioning
confidence: 99%